The Role of Supply Chain Collaboration in Achieving Carbon Neutrality : Evidence from Global Logistics Companies - Lawrance, Shashini (My University, 2026)
The paper examines the importance of supply chain collaboration in attaining carbon neutrality in the logistics industry using evidence of global logistics firms. The study discusses the increased significance of minimizing carbon emissions in supply chains especially since transportation, warehousing, and distribution of logistics operations are major sources of greenhouse gas emissions on the earth. Although the need to be sustainable and collaborative is mentioned in the previous literature, the practicality of the logistics companies to work with the supply chain partners to attain carbon-neutral results is still not well comprehended empirically. This research adopts a qualitative mono-method design by adopting an interpretivist research philosophy and a deductive approach. Semi-structured interviews conducted with four Finnish, Australian and Sri Lankan logistics professionals were used to collect the data. A qualitative thematic analysis was used to analyze the data collected. The results demonstrate that logistics firms are at the center of coordination to mitigate supply chain emissions by collaborating in several practices that include shipment consolidation, route optimization, demand planning, and information sharing. They found digital tools, such as Transportation Management Systems (TMS) and Warehouse Management Systems (WMS) as primary enablers of transparency and coordination. Nevertheless, the article also reveals that there are numerous obstacles to successful cooperation, such as the absence of data transparency, the incompatibility of sustainability objectives, financial limitations, and technological disparities between partners. The study also shows that carbon neutrality in logistics is not possible through individual organizational actions but must be carried out by joint, data-driven actions at all levels of the supply chain. The research adds to the literature in the field by offering practical information on collaboration mechanisms, difficulties and facilitating factors in the logistics perspective. It also has managerial implications as it highlights that better collaboration between partners in reducing carbon requires that they should be standardized in the data system, stronger partnerships, and increased investment in sustainable technologies.
Keywords: supply chains; logistics; emissions; cooperation (general); carbon neutrality; green economy; Sustainable Development Goals; transport companies; carbon footprint; fi=Taloustiede|en=Economics|; Master’s Programme in Strategic Business Development